Targeted adsorption of molecules in the colon with the novel adsorbent‐based Medicinal Product, DAV132: A proof of concept study in healthy subjects. (16th July 2014) - de Gunzburg, Jean; Ducher, Annie; Modess, Christiane; Wegner, Danilo; Oswald, Stefan; Dressman, Jennifer; Augustin, Violaine; Feger, Céline; Andremont, Antoine; Weitschies, Werner; Siegmund, Werner
Abstract During antibiotic treatments, active residuals reaching the colon profoundly affect the bacterial flora resulting in the emergence of resistance. To prevent these effects, we developed an enteric‐coated formulated activated‐charcoal based product, DAV132, meant to deliver its adsorbent to the ileum and neutralize antibiotic residues in the proximal colon. In a randomized, control, crossover study, the plasma pharmacokinetics of the probe drugs amoxicillin (500 mg) absorbed in the proximal intestine, and sulfapyridine (25 mg) metabolized from sulfasalazine in the cecum and rapidly absorbed, were compared after a single administration in 18 healthy subjects who had received DAV132, uncoated formulated activated charcoal (FAC) or water 16 and 8 hours before, concomitantly with the probe drugs, and 8 hours thereafter. The AUC0–96 h of amoxicillin was reduced by more than 70% when it was taken with FAC, but bioequivalent when it was taken with water or DAV132. By contrast, the AUC0–96 h of sulfapyridine was reduced by more than 90% when administered with either FAC or DAV132 in comparison with water. The results show that DAV132 can selectively adsorb drug compounds in the proximal colon, without interfering with drug absorption in the proximal small intestine, thereby constituting a proof of concept that DAV132 actually functions in humans.